OPTIMALISASI KESAMAPTAAN JASMANI PRAJURIT AKADEMI MILITER MAGELANG - Burhanudin, Sambas; Supriyono, Tjatur; Muliani (JURNAL DWIJA KUSUMA, 2023)
Physical ability for every soldier is an important factor and the main support for both a career and in carrying out tasks. So that the physical abilities of soldiers can be increased, it is necessary to formulate or create a correct and measurable physical development program that can be used as a basic guideline for Indonesian Army soldiers which can be implemented both individually and as a unit. The research objectives to be obtained related to this research are to determine the physical fitness activities of Military Academy Soldiers carried out by the Department of Physical Education and to analyze the efforts made in improving the Physical Competence of Military Academy Soldiers. This research is a qualitative research which is research used to examine the conditions of natural objects where the researcher is the key instrument. Efforts to increase the physical abilities of soldiers within the Military Academy are by training and fostering physical abilities in stages, stages and continuously by implementing appropriate training programs according to task requirements and avoiding injuries, optimizing the role of the Physical Department in forming a good mental attitude in which a unit commander in The Magelang Military Academy must be able to provide explanations to its members about the attitudes and behavior of soldiers as a guide to foster motivation and dedication in carrying out their duties